Index JCS - JCS Volume 4 (Journal of Consumer Sciences, 2019)
JCS VOL 04 NO 01Ajzen 40ANOVA 57assets ownership 27clinic 15entrepreneurial families 27experiments 50fast food 50financial knowledge40financial management 27intention  39, 50knowledge 39, 50KPA 4KPR 4marketing mix 3, 15mortgage product 3partial least square analysis 3participatory decision-making 11perceived risk 15perception of risk 18PLS 41purchase decision 3religiosity 39retirement financial planning 40risk perception 39risk tolerance 40satisfaction 15SEM 6, 41sharia insurance 40social media 19soft drink 50STP 11Students 52subjective well-being 27Sumarwan 40TPB 39word of mouth  15 JCS VOL 04 NO 02brand image 76CB-SEM 81Clinic 107consumers 90Development 107Entrepreneurs 72ethnocentrism 61Financial variables 119generation Y 61Health services 109initial return behavior 119investor behavior 119IPO 120loyalty 90non-financial variables 119PLS-PM 66preference 61product quality 72purchase intention 76purchasing decisions 61QSPM 110, 114reference group 61Retail 62satisfaction 90SDGs 107self-concept 76SERVQUAL 90SmartPLS 84social media 76social media influencer 76Strategy 107SWOT 110underpricing 119